Antibakteri PERBANDINGAN AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL KULIT MELINJO HIJAU DAN MERAH (Gnetum gnemon L) TERHADAP Staphylococcus aureus: PERBANDINGAN AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL KULIT MELINJO HIJAU DAN MERAH (Gnetum gnemon L) TERHADAP Staphylococcus aureus - diva nadia humaira; Noni Zakiah; Vonna Aulianshah (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2023)
Along with the increase in bacterial resistance in the world of health, it is necessary to find new drugs. Melinjo skin has components of bioactive compounds that are thought to have antibacterial potential. this research aims to determine the antibacterial in inhibition ability of the ethanol extract of green and red melinjo peels (Gnetum gnemon L) againts Staphylococcus aureus. This research was experimental, the antibacterial test used the disc diffusion method with a Completely Randomized Design (CRD) which was divided into 3 treatments namely aquades (P0) green melinjo peel extract (P1) red melinjo peel extract (P2) with 6 repetitions each. Phytochemical test results showed that the ethanol extract of green and red melinjo peels contained alkaloids, steroids, terpenoids, flavonoids, phenolics and tannins. The result of the ANOVA test showed that the ethanol extract of green and red melinjo peels was very influential in inhibiting the growth of Staphylococcus aureus (P=0,000). Further Duncan test results showed that the largest average diameter of the inhibiyion zone was the green melinjo peel extract (15,9 mm) and was significantly different from the red melinjo peel extract (10 mm). Green and red melinjo peel extract can inhibit Staphylococcus aureus`